2014
DOI: 10.1371/journal.pone.0092948
|View full text |Cite|
|
Sign up to set email alerts
|

AKT Inhibitors Promote Cell Death in Cervical Cancer through Disruption of mTOR Signaling and Glucose Uptake

Abstract: BackgroundPI3K/AKT pathway alterations are associated with incomplete response to chemoradiation in human cervical cancer. This study was performed to test for mutations in the PI3K pathway and to evaluate the effects of AKT inhibitors on glucose uptake and cell viability.Experimental DesignMutational analysis of DNA from 140 pretreatment tumor biopsies and 8 human cervical cancer cell lines was performed. C33A cells (PIK3CAR88Q and PTENR233*) were treated with increasing concentrations of two allosteric AKT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 34 publications
5
58
1
Order By: Relevance
“…This interaction between Sirt2 and Akt is required to allow optimal Akt activation. In this sense, previous evidence has revealed that Akt inhibitors effectively block the mammalian target of rapamycin complex 1 (mTORC1; containing mTOR and RAPTOR) and decrease glucose uptake, glycolytic rate and cell viability (Rashmi et al, 2014). In agreement with our above results, it has been concluded previously that mTOR-RAPTOR promotes Glut1 activity but does not regulate Glut1 surface localization (Wieman et al , 2007).…”
Section: Stimulation Of Glut1-mediated Glucose Uptake By Acute Oxphossupporting
confidence: 92%
See 1 more Smart Citation
“…This interaction between Sirt2 and Akt is required to allow optimal Akt activation. In this sense, previous evidence has revealed that Akt inhibitors effectively block the mammalian target of rapamycin complex 1 (mTORC1; containing mTOR and RAPTOR) and decrease glucose uptake, glycolytic rate and cell viability (Rashmi et al, 2014). In agreement with our above results, it has been concluded previously that mTOR-RAPTOR promotes Glut1 activity but does not regulate Glut1 surface localization (Wieman et al , 2007).…”
Section: Stimulation Of Glut1-mediated Glucose Uptake By Acute Oxphossupporting
confidence: 92%
“…In order to assess the potential involvement of Akt in the piericidin-A-and antimycin-A-induced increase in glucose uptake, we tested the pan-Akt inhibitor SC-66 (Jo et al, 2011). Pretreatment with SC-66 (10 μg/ml, 1 h) (Rashmi et al, 2014) did not reduce the stimulation of glucose uptake in inhibitor-treated cells (data not shown). Assuming that the effect of SC-66 is Akt specific, this result argues against involvement of Akt in the stimulation of glucose uptake.…”
Section: Stimulation Of Glut1-mediated Glucose Uptake By Acute Oxphosmentioning
confidence: 99%
“…Prior studies have shown anticancer activity of MK-2206 across multiple tumor types as well as synergy with established chemotherapeutic agents in NSCLC (Agarwal et al 2014; Almhanna et al 2013; Hirai et al 2010; Konopleva et al 2014; Rashmi et al 2014). Additional work has indicated synergy and enhanced cytotoxicity when MK-2206 is combined with EGFR inhibitors including erlotinib, gefitinib, and cetuximab in the context of a limited number of NSCLC, breast, and glioma cell lines (Cheng et al 2012; Hirai et al 2010; Iida et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…PTEN mutations were frequently found in cancers arising from the endometrium 29,30 , brain 31 and prostate 32 . Rashmi et al 33 found results with activating PIK3CA (E545K, E542K) and inactivating PTEN (R233) mutations were identified in human cervical cancer. An analysis of PTEN gene in squamous cell carcinomas from other sites also found that PTEN is not frequently mutated in the lung 34 , cervix 14 , skin 35 , head and neck 36 or esophagus 37 .…”
Section: Discussionmentioning
confidence: 99%